Pengaruh Keselamatan dan Kesehatan Kerja Terhadap Kinerja Karyawan PT. Gapura Angkasa Unit Passasi Bandar Udara Internasional Juanda Surabaya di masa Pandemi Covid-19 - Dandy Fahmi Yunus (Jurnal Multidisiplin Madani, 2022)
This study aims to determine (1) the effect of occupational safety on employee performance, (2) the effect of occupational health on employee performance, (3) the effect of occupational safety and health on employee work performance. This research uses a quantitative approach. The sampling technique in this study used a saturated sampling technique of 50 employees of the passasi unit of PT. Gapura Angkasa Juanda International Airport, Surabaya. The data collection technique uses direct questionnaires, the data that has been studied can then be analyzed through multiple linear analysis. This research was conducted in September 2021. Based on the results of the study, it was shown that (1) work safety had a significant effect on the work performance of employees of PT. Gapura Angkasa Juanda International Airport Surabaya, (2) occupational health has a significant effect on the work performance of PT. Gapura Angkasa Bandarr Juanda International Airport, Surabaya, (3) occupational safety and health simultaneously or simultaneously have a significant effect on the work performance of PT. Gapura Angkasa, Juanda International Airport, Surabaya, amounted to 28.2% with a sig value of 0.000 <0.05.